Respon Tanaman Gandum (Triticum aestivum L.) Varietas Dewata 162 terhadap Pemberian Mikoriza dan Pupuk Kalium - Adityani (Indoensia), Widowati; Susilowati (Indoensia), Yulia Eko; Iftitah (Indoensia), Siti Nurul (Universitas Tidar, 2023)
Research on the response of wheat plants to the application of mycorrhizae and K fertilizer was carried out from October 16, 2021 to January 25, 2022. The study was conducted in Selopampang Village, Selopampang District, Temanggung Regency with an altitude of 670 m above sea level. The research method used a factorial experiment (4 x 3) arranged in a Completely Randomized Block Design (RAKL) with two treatment factors and repeated three times. The first factor was the dose of mycorrhizae 2,5 g/plant, 5 g/plant, 7,5 g/plant and 10 g/plant. The second factor was the dose of potassium 17,5 kg/ha, 35 kg/ha and 52,5 kg/ha. Data were analyzed by means of variance. The influential results were further tested using orthogonal polynomials. The results showed that the high of mycorrhizae dose increase the dry weight of seed per clump. Potassium fertilizer with a dose of 52,5 kg/ha gave the highest yield on the dry weight of seed per clump. Mycorrhizae 10 g/plant and K fertilizer 52,5 kg/ gave the highest yield on the dry weight of seed per clump.